Math, asked by Shanu3583, 1 year ago

√2x+√3y=0 √3x-√8y=0 cross multiplication method

Answers

Answered by ColinJacobus
8

Answer:  The required solution to the given system is

x = 0,  y = 0.

Step-by-step explanation:  We are given to solve the following system of equations by the method of cross-multiplication :

\sqrt2x+\sqrt3y=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\\sqrt3x-\sqrt8y=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)

The table of cross-multiplication is as follows :

      x             y              1

√3        0              √2           √3

-√8       0               √3          -√8

Therefore, by the method of cross-multiplication, we get

\dfrac{x}{\sqrt3\times0-0\times(-\sqrt8)}=\dfrac{y}{0\times\sqrt3-\sqrt2\times0}=\dfrac{1}{\sqrt2\times(-\sqrt8)-\sqrt3\times\sqrt3}\\\\\\\Rightarrow \dfrac{x}{0}=\dfrac{y}{0}=\dfrac{1}{-4-3}\\\\\\\Rightarrow x=\dfrac{0}{-7}=0,~~y=\dfrac{0}{-7}=0.

Thus, the required solution to the given system is

x = 0,  y = 0.

Answered by knjroopa
5

Answer:

x = 0, y = 0

Step-by-step explanation:

Given  

√2x+√3y=0 √3x-√8y=0 cross multiplication method

 given √2 x + √3 y = 0------------1

from second equation we get

√3 x - √8 y = 0----------2

 y = √3 x / √8 ------------3

 substituting y we get

 √2 x + √3 (√3 x / √8) = 0

 √2 x + 3x / √8 = 0

  √16 x + 3 x = 0

       4 x + 3 x = 0

            7 x = 0

                  x = 0

substituting x = 0 in equation 3 we get

          y = √3 x 0 / √8

           y = 0

So x = 0, y = 0

Similar questions